Kidney transplantation in patients with multiple myeloma: narrative analysis and review of the last two decades. Issue 9 (9th December 2020) - Chitty, David W; Hartley-Brown, Monique A; Abate, Mersema; Thakur, Richa; Wanchoo, Rimda; Jhaveri, Kenar D; Nair, Vinay
Abstract: There have been significant advances in the treatment of multiple myeloma in the last two decades. Approximately 25% of patients with newly diagnosed myeloma have some degree of kidney impairment. During the course of illness, nearly 50% of myeloma patients will develop kidney disease. Moreover, ∼10% of myeloma patients have advanced kidney disease requiring dialysis at presentation. Hemodialysis is associated with a significantly reduced overall survival (OS). In the setting of prolonged long-term OS due to the use of newer immunotherapeutic agents in the treatment of myeloma, patients with myeloma and advanced kidney disease may benefit from more aggressive management with kidney transplantation (KTx). Unfortunately, most data regarding outcomes of KTx in patients with myeloma come from single-center case series. With the advent of novel treatment choices, it remains unclear if outcomes of kidney transplant recipients with myeloma have improved in recent years. In this descriptive systematic review, we coalesced published patient data over the last 20 years to help inform clinicians and patients on expected hematologic and KTx outcomes in this complex population. We further discuss the future of KTx in patients with paraproteinemia.